Pengaruh Ukuran Perusahaan Dan Solvabilitas Terhadap Opini Audit Going Concern - Hana Simamora; Lembah Dewi Andini (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2023)
Purpose: This study aims to determine the effect of Firm Size and Solvability on Going Concern Audit Opinions. Design/methodology/approach: This research uses quantitative data, the sample in this study is chemistry basic materials, agricultural chemistry, special chemistry and construction materials companies sector which are listed on the Indonesia Stock Exchange in the period 2018 – 2022 as many 17 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings: The results of this study indicate that the Firm Size has a positive and statistically insignificant effect on Going Concern Audit Opinions and the Solvability has a positive and statistically insignificant effect on Going Concern Audit Opinions. Originality/value: This study discusses Going Concern Audit Opinions and other factors such as Firm Size and Solvability which focus on chemistry basic materials, agricultural chemistry, special chemistry and construction materials companies sector. This study uses the dummy variable as a measurement of Going Concern Audit Opinions.